The Influence of Perceived Organizational Support and Competence on Employee Performance, with Job Satisfaction as a Mediating Variable in BCA Express Jabodetabek - Tarigan, Joy Evan Saimara; Sadana, Stefanus M. Sri; Siagian, Bekman; Winarto, Oetami P. (Dinasti International Journal of Management Science, 2026)
This study aims to examine the effect of perceived organizational support (POS) and competence on employee performance, with job satisfaction as a mediating variable at Bank Central Asia (BCA) Express Jabodetabek. A quantitative approach with causal and associative properties was used through hypothesis testing. The population consists of all 93 customer service employees (census). Data analysis uses the Partial Least Squares (PLS) method with the help of SmartPLS 4.0 software. The findings of the study are that POS, competence, and job satisfaction directly have a significant effect on performance. POS and competence also directly have a positive and significant effect on job satisfaction. Job satisfaction acts as a mediating variable that strengthens the influence of POS and competency on performance. Increased job satisfaction strengthens the contribution of organizational support and competency to employee performance.